Pulmonary and extra-pulmonary infections caused by classical and hypervirulent Klebsiella pneumoniae: a prospective cross-sectional study - Alshehri, Fatma; Mosbah, Rasha A.; Abdelkhalig, Sozan M.; Alblwi, Noaf Abdullah N.; Fawzy, Shereen; Alshareef, Hanan; Ahmed, Rehab; Zaitone, Sawsan A.; Mohamed, Abir S.; Mansour, Abdallah Tageldein; Alhomrani, Majid; Alamri, Abdulhakeem S.; et al. (Frontiers in Microbiology, 2026)
AimKlebsiella pneumoniae (K. pneumoniae) is an opportunistic pathogen causing infections ranging from pulmonary disease to severe systemic illness. This study aimed to examine the relationships between infection site, pathotype, virulence, resistance, and clinical presentations to manage classical (cKp) and hypervirulent (hvKp) strains.Methods and results600 clinical specimens were screened for K. pneumoniae. Virulence and resistance fitness were analyzed phenotypically and genotypically. Clinical correlations were assessed to link pathotype, resistance, virulence, infection site, age, and presentation. K. pneumoniae was detected in 17.2% specimens (103/600), with pulmonary samples showing 43% positivity versus 12% in extra-pulmonary ones. hvKp accounted for 55.3% and cKp for 44.7% of isolates; hvKp predominated in extra-pulmonary infections (83.3%) and cKp in pulmonary cases (83.7%). K1 (33.1%) and K2 (21.4%) were confined to hvKp, while pulmonary isolates were mainly K3, K5, and K20. Pulmonary infections mainly affected adults (81.4%) and showed respiratory signs; extra-pulmonary cases occurred mostly in pediatric (46.7%) and elderly (41.7%) patients with systemic symptoms such as fever and hypotension. Clustering distinguished pulmonary/cKp (MDR-rich) from extra-pulmonary/hvKp (virulence-rich) isolates, with some overlap indicating hybrid strains. Correlations linked pulmonary infections with cKp and MDR (r = 0.67), and extra-pulmonary infections with hvKp and systemic disease (r = 0.67).ConclusionThe high MDR burden of cKp underscores the need for stronger antimicrobial stewardship and new therapies, while the invasive nature of hvKp highlights the importance of early recognition and rapid intervention to prevent systemic complications. Early distinction of cKp from hvKp can significantly influence treatment decisions and reduce morbidity and mortality associated with K. pneumoniae infections.